2019
DOI: 10.1021/acs.est.8b05870
|View full text |Cite
|
Sign up to set email alerts
|

Criteria Air Pollutant and Greenhouse Gases Emissions from U.S. Refineries Allocated to Refinery Products

Abstract: Using Greenhouse Gas Reporting Program data (GHGRP) and National Emissions Inventory data from 2014, we investigate U.S. refinery greenhouse gas (GHG) emissions (CO 2 , CH 4 , and N 2 O) and criteria air pollutant (CAP) emissions (VOC, CO, NO x , SO 2 , PM 10 , and PM 2.5 ). The study derives (1) combustion emission factors (EFs) of refinery fuels (e.g., refinery catalyst coke and refinery combined gas), (2) U.S. refinery GHG emissions and CAP emissions per crude throughput at the national and regional levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…A previous investigation into greenhouse gas (GHG) emissions produced from plastic-tofuel technology showed a 96 % reduction in GHG compared to traditional fuel, [39] while another study showed lubricants to produce the most GHGs in U.S. refineries compared to other refinery products. [40] Circumventing GHG emissions from lubricant production in a way similar to plastic-to-fuel technology would thus prove invaluable for combatting environmental challenges. An initial life cycle analysis (LCA) best exemplifies this efficient renewal by highlighting an energy efficiency of 96.9 % given a conceptual plant with 250 Mt per day capabilities.…”
Section: Resultsmentioning
confidence: 99%
“…A previous investigation into greenhouse gas (GHG) emissions produced from plastic-tofuel technology showed a 96 % reduction in GHG compared to traditional fuel, [39] while another study showed lubricants to produce the most GHGs in U.S. refineries compared to other refinery products. [40] Circumventing GHG emissions from lubricant production in a way similar to plastic-to-fuel technology would thus prove invaluable for combatting environmental challenges. An initial life cycle analysis (LCA) best exemplifies this efficient renewal by highlighting an energy efficiency of 96.9 % given a conceptual plant with 250 Mt per day capabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Roughly speaking, the adhesive also belongs to the category of rubber [15], and the adhesive is mainly composed of basic rubber, hardener, filler, coupling agent, catalyst, and so on. With the rapid development of China's real estate, packaging materials, building materials, etc., the amount of glue has increased sharply.…”
Section: Application Of Nano-calcium Carbonate In Adhesivementioning
confidence: 99%
“…Moreover, in a paper about the U.S. refining scenario from 2014 [49], an EF for VOCs was evaluated in a range of 80-110 g/ton (this value was obtained after conversion of the data proposed, which were reported as g/MJ of energy consumed), which in turn is also very similar to the EF proposed here.…”
Section: Estimation Of An Emission Factor (Ef) For Total Voc Emissionsmentioning
confidence: 78%